Efficacy and safety of 100% TCA CROSS for atrophic acne scar: A systematic review - Satmoko, Valentino Yosarian; Elfiah, Ulfa; Aziz, Ayu Munawaroh (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Acne scars result from impaired healing following skin inflammation, with atrophic acne scars accounting for 98% of cases. Although various treatments are commonly used, no gold-standard therapy exists. Chemical reconstruction of skin scars using 100% trichloroacetic acid (100% TCA CROSS) has emerged as a novel intervention for atrophic acne scars. However, evidence supporting its efficacy and safety remains limited, necessitating further evaluation. This systematic review was conducted in accordance with PRISMA and SWiM guidelines. Literature searches were performed in PubMed, Cochrane Library, Google Scholar, and ScienceDirect. Studies were included if they involved patients with atrophic acne scars and utilized 100% TCA CROSS as the intervention, with comparators comprising other acne scar treatments. The primary outcome was efficacy, and the secondary outcome was safety. Only randomized controlled trials (RCTs) were included. Two independent reviewers assessed risk of bias, extracted data, and conducted qualitative analysis. Six studies met the eligibility criteria, with comparators including CO2 laser pinpoint irradiation, microneedling, percutaneous collagen induction dermaroller, platelet-rich plasma (PRP) injection, and PRP injection with needling. One study favored the comparator, while five studies demonstrated no clear difference. Within-group analyses indicated improvements following 100% TCA CROSS. No severe complications were reported. Meta-analysis was not performed due to heterogeneity in outcome measures. In summary, 100% TCA CROSS appears effective and safe for atrophic acne scars.